2010
DOI: 10.1212/wnl.0b013e3181d9edba
|View full text |Cite
|
Sign up to set email alerts
|

COMT genotype and cognitive function

Abstract: Objective: Catechol-O-methyltransferase (COMT), an enzyme that catalyzes the degradation of dopamine, is necessary for cognitive function. Few studies have examined the prospective association between COMT (val 158 met) genotype and cognition in older adults. Methods:We assessed a biracial cohort of 2,858 elderly subjects without dementia who were followed for 8 years. The Modified Mini-Mental State Examination (3MS) and Digit Symbol Substitution Test (DSST) were administered at baseline and years 3, 5, and 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…Directly testing of catechol-O-methyltransferase enzymatic activity and delirium would have a higher sensitivity to pick up any association with the susceptibility to delirium. However, it was shown that these polymorphisms were associated with syndromes with comparable symptoms like hyperactivity in attention deficit hyperactivity disorder [25], schizophrenia [26], psychosis in Alzheimer’s dementia [23] and cognitive decline [7]. The results of the rs4680 polymorphisms are in line with former studies looking at the association with alcohol withdrawal delirium [27].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Directly testing of catechol-O-methyltransferase enzymatic activity and delirium would have a higher sensitivity to pick up any association with the susceptibility to delirium. However, it was shown that these polymorphisms were associated with syndromes with comparable symptoms like hyperactivity in attention deficit hyperactivity disorder [25], schizophrenia [26], psychosis in Alzheimer’s dementia [23] and cognitive decline [7]. The results of the rs4680 polymorphisms are in line with former studies looking at the association with alcohol withdrawal delirium [27].…”
Section: Discussionsupporting
confidence: 67%
“…The catechol-O-methyltransferase protein is encoded by the COMT gene, located on 22q11.1–q11.2. Current research suggests an association between cognitive decline and the COMT gene [7] and between psychosis in Alzheimer’s dementia and polymorphisms in the COMT gene [8]. The most well-studied is Val158Met (rs4680) that has been shown to affect cognitive tasks broadly related to executive function [9].…”
Section: Introductionmentioning
confidence: 99%
“…An interaction of COMT and age was identified for middle-aged participants (aged 50-60), supporting the idea that discrepancies due to genetic effects are greater in midlife than in aging. Fiocco et al [14] identified a difference in cognitive decline across an 8-year interval, such that individuals with a homozygous Val/Val genotype displayed significantly less decline in the Digit Symbol Substitution Test performance compared to Met homozygotes, indicating an approximation of different genotypes in test performance in the course of healthy aging. Generally, the respective studies are in line with our findings, even though we did not identify an interaction effect of time (age) and the COMT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…De Frias et al [13] found Val/Val carriers' performance on tasks of executive functioning to decline over a 5-year interval in contrast to Met carriers and identified a COMT × age interaction for middle-aged adults (50-60 years). Fiocco et al [14] found the opposite, such that individuals (aged 70-79) with a homozygous Val/Val genotype displayed significantly less decline in the performance on the Digit Symbol Substitution Test than carriers of the Met/Met genotype across an 8-year interval, indicating an approximation of genotypes in cognitive test performance in aging. Other longitudinal studies have found no genetic impact on cognitive decline (n = 53, mean age 75.5, SD = 5.3 [15]; n = 473, age 64-68 [16]).…”
Section: Introductionmentioning
confidence: 99%
“…The DSST score is calculated as the total number of items correctly coded in 90 s, with a higher score indicating better cognitive function. Participant-specific slopes of DSST scores were estimated from mixed-effects models with random intercepts and slopes [94]. The participant-specific slopes of 3MS scores were estimated by best linear unbiased predictions using a linear mixed model with random intercepts and slopes using STATA10.…”
Section: Methodsmentioning
confidence: 99%